Moya Moya disease: Report of 2 cases and review of literature - Showkat, MS; Nuruzzaman, S; Datta, A (Community Based Medical Journal, 2013)
Moya moya disease is a chronic cerebral vasculopathy characterized by progressive occlusion of circle of Willis arteries that leads to development of collateral vessel which has a characteristic puff of smoke appearance on imaging. Here we described 2 cases, both were young and presented with history of stroke and repeated headache. In Magnetic Resonance Angiogram (MRA), we found marked narrowing in internal carotid, anterior, middle and posterior cerebral artery with multiple collaterals producing puff of smoke appearence which is the diagnostic imaging feature of Moya Moya disease. This is an important cause of repeated stroke in young patients. So physicians should be aware of this clinical entity. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16705 Community Based Medical Journal 2013 July: Vol.02 No 02: 77-80